Comparative evaluation between KOH and PAS stain of fungal examination result on lung Tuberculosis patients’ sputum with positive Ziehl-Neelsen stain - Ratna Kusumawati; Eddy Bagus Wasito; Arthur Pohan Kawilarang; Eko Budi Koendhori (Universitas Muhammadiyah Surabaya, 2023)
Mycosis is often misdiagnosed as Tuberculosis (TB) with negative sputum smear results or Tuberculosis recurrent. In the last two-decade, mycosis increases dramatically as HIV and immunocompromised incidence rates increased. Even though, the prevalence data of mycosis in TB patient is less researched, the identification using KOH often give a false negative result. To compare the result of fungal identification using KOH and PAS staining. This study is observational analytical using a cross-sectional design with 29 TB samples that have been diagnosed with Ziehl-Neelsen (ZN) stain positive in RSUD Dr. Soetomo. The sputum of every sample was colored with KOH and PAS and observed by the researcher and microbiology analyst. The results of this study were 22 sputa identified with Candida sp positive and 12 sputa with non-Candida positive using KOH staining. Meanwhile, using PAS staining, there were 25 sputa identified as Candida sp positive and 22 sputa as non-Candida positive. The congruency test between KOH and PAS has a fair result for both identifying Candida sp (κ = 0.298; significance = 0.069) and non-Candida (κ = 0.240; significance = 0.095). The identification of candida and non-candida in TB patients using KOH and PAS has a fair congruency result. The PAS staining has better identification results both in identifying candida and non-candida rather than KOH staining.